DEVELOPMENT AND VALIDATION OF A TLC DENSITOMETRIC METHOD FOR DETERMINATION OF GLIMEPIRIDE IN TABLETS - Yuni Retnaningtyas; Lestyo Wulandiri; Gabriella F Punu (Jurnal Kimia Terapan Indonesia, 2014)
A simple and valid TLC method has been developed for the determination of glimepiride in tablet formulation. After extraction of the analyte with a mixture of methanol and ammonia 0,2M (1:1, v/v), the extracts were spotted on precoated TLC silica gel F254 plates, which were developed with a mixture of toluene:methanol:ethyl acetate (75:20:5, v/v/v). Quantitative evaluation was performed by measuring the absorbance reflectance of the analyte spots at 238 nm. The method was validated for specificity, linearity, accuracy and precision. Good linearity was achieved in the concentration range 100â€“800 ng/spot. The RSD of repeatability and intermediate precision were found to be less than 2%, whereas the mean of the recovery data was 100-101%. The detection limit and quantification limit were 22 and 74 ng/spot, respectively. The method is specific, linear, precise, and accurate; it can be used for the routine quality control testing of marketed formulations.Keywords: glimepiride, TLC densitometric, validation of pharmaceutical methods, pharmaceutical analysis, antidiabetic drugÂ Sebuah metode Kromatografi Lapis Tipis (KLT) yang sederhana dan valid telah dikembangkan untuk penentuan glimepiride dalam sediaan tablet. Setelah analit dalam sampel diekstraksi dengan campuran metanol dan amonia 0,2 M (1:1,v/v), ekstrak yang terlihat pada lempeng silika gel F254, yang dikembangkan dengan campuran toluen : metanol : etil asetat (75:20:5, v/v/v). Evaluasi kuantitatif dilakukan dengan mengukur reflektansi absorbansi noda analit pada panjang gelombang 238 nm.Metode ini divalidasi meliputi spesifisitas, linearitas, akurasi dan presisi.Linearitas yang baik dicapai pada rentang konsentrasi 100-800 ng / spot. RSD pengulangan dan presisi intermediate menunjukkan nilai kurang dari 2 %, sedangkan rata-rata data recovery adalah 100-101 % .Batas deteksi dan batas kuantifikasi adalah 22 dan 74 ng / noda.Metode ini spesifik, linear, tepat, dan akurat, bisa digunakan untuk pengujian kontrol kualitas rutin tablet glimepirid dipasarkan. Kata Kunci: glimepiride, TLC densitometric, validation of pharmaceutical methods, pharmaceutical analysis, antidiabetic drug